2020
DOI: 10.18332/tpc/115064
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of packaged smokeless tobacco sold in India

Abstract: INTRODUCTION About 21.4% of India's population uses smokeless tobacco products (SLT), yet limited data are available on their microbial contamination. To understand the potential microbiological risks associated with SLT use, the present study aims to investigate bacterial contamination of tobacco and the types of microbes that could be cultured from SLT products. METHODS Twenty-two brands of SLT products, including paan masala, khaini, gutka and tobacco-containing dentifrices were examined and cultured by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The study found that the most commonly isolated bacteria were Pseudumonas aeruginosa, Streptococcus faecalis, E. coli and Klebsiella pneumonia. 12 A study by Han J et al, Rubeinstein I et al from United States of America and Yusuf OAA et al from South Africa also found that the predominant species were from the class of Bacillus. [13][14][15] A study done in Nigeria exclusively among snuff products showed that the colony counts ranged from 3.0x10 2 CFU/gm to 6.7x10 2 /gm while our study showed higher bacterial counts.…”
Section: Discussionmentioning
confidence: 96%
“…The study found that the most commonly isolated bacteria were Pseudumonas aeruginosa, Streptococcus faecalis, E. coli and Klebsiella pneumonia. 12 A study by Han J et al, Rubeinstein I et al from United States of America and Yusuf OAA et al from South Africa also found that the predominant species were from the class of Bacillus. [13][14][15] A study done in Nigeria exclusively among snuff products showed that the colony counts ranged from 3.0x10 2 CFU/gm to 6.7x10 2 /gm while our study showed higher bacterial counts.…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that a few of the more recent studies (Al-Hebshi et al 2017 ; Mehra et al 2020 ; Zhang et al 2020 ; Zhou et al 2020 ) focus mainly on products or aging tobacco not widely available in the USA. While “international” products are quite interesting, especially in the capacity that some products such as Sudanese toombak, Yemeni Shammah, and Asian betel quid contain higher amounts of carcinogenic TSNAs as compared with US domestic products, we will forego discussing them in this review in order to focus on US domestic products.…”
Section: Smokeless Tobacco Harbors Diverse Microbial Communitiesmentioning
confidence: 99%
“…The microbiota has been previously reported in cured tobacco leaves and STPs using both culture-dependent and culture-independent approaches (Di Giacomo et al, 2007;Han et al, 2016;Tyx et al, 2016;Smyth et al, 2017;Mehra et al, 2020). The microbiome of tobacco products participates in the synthesis of TSNAs.…”
Section: Introductionmentioning
confidence: 99%